EDTA Chelation Therapy in the Treatment of Neurodegenerative Diseases: An Update - Alessandro Fulgenzi; Daniele Vietti; Maria Elena Ferrero (Biomedicines, 2020)
We have previously described the role played by toxic-metal burdens in the etiology of neurodegenerative diseases (ND). We herein report an updated evaluation of toxic-metal burdens in human subjects affected or not affected by ND or other chronic diseases. Each subject underwent a chelation test with the chelating agent calcium disodium ethylenediaminetetraacetic acid (CaNA2EDTA or EDTA) to identify the presence of 20 toxic metals in urine samples using inductively coupled plasma mass spectrometry. Our results show the constant presence of toxic metals, such as lead, cadmium, cesium, and aluminum, in all examined subjects but the absence of beryllium and tellurium. Gadolinium was detected in patients undergoing diagnostic magnetic resonance imaging. The presence of toxic metals was always significantly more elevated in ND patients than in healthy controls. Treatment with EDTA chelation therapy removes toxic-metal burdens and improves patient symptoms.